Pengembangan Lembar Kerja Siswa Untuk Pembelajaran Model Discovery Learning Pada Materi Hidrolisis Garam Di SMA - Triliyansi Triliyansi; Abudarin Abudarin; Akhmad Damsyik; Agus Haryono; Abdul Hadjranul Fatah; Sri Rohaetin (Jurnal Ilmiah Kanderang Tingang, 2023)
The implementation of the discovery learning model is that students are able to construct their own knowledge that they must master through 6 (six) stages of learning discovery, namely: (i) stimulation; (ii) problem statements; (iii) data collection;(iv) data processing; (v) verification; (vi) generalization. In its application, students need a study guide to be able to carry out discovery learning activities independently to obtain new knowledge, this research aims to produce a Student Worksheet (LKS) as a learning guide in learning salt hydrolysis with a discovery learning model in class XI high school students. The development of LKS was carried out by adapting the 4-D development model (define, design, d evelop, disseminate) from Thiagarajan. The resulting LKS products are assessed for feasibility using professional judgement by involving chemists, pedagogists, and learning media experts. The revised LKS product based on expert input is then tested for readability by potential users. Furthermore, LKS is implemented on a limited basis in chemistry learning in schools to determine its effectiveness in guiding discovery learning activities and improving students' understanding of the concept of salt hydrolysis. The limited implementation trial was carried out using a pre-experimental design of the One-Shot Case Study model involving 69 high school students in Palangka Raya city. The results showed that the LKS developed was suitable for use with a feasibility value of 92.45%. The effectiveness of LKS in guiding students to carry out discovery learning activities is in the very good category with an average of 97.75% and LKS is effective in improving students' mastery of the concept of salt hydrolysis by obtaining an average N-Gain score of 0.89.